Determinants of Financial Sector Performance on Economic Growth of Sharia and Conventional Banks: Case Study in OIC Countries - Izzun Khoirun Nissa (Mutanaqishah: Journal of Islamic Banking, 2024)
This research aims to analyze the influence of financial sector developments on the economic growth of sharia and conventional banking in twelve Islamic countries during the 2015-2022 period. This research uses panel data to provide empirical estimates involving 12 Islamic countries during the 2015-2022 period. We collected secondary data from the World Bank. The study's results indicate that the variables of interest rate, total assets of conventional banks, financing, and total assets of Islamic banks do not significantly impact economic growth. Meanwhile, the deposit variable has a negative effect, and the number of Islamic banks has a positive effect on economic growth. In the meantime, examining the impact of the sharia financial sector on economic growth reveals that the financing variables and the number of sharia offices significantly boost economic growth. The variable total assets of Islamic banks have no effect on economic growth. This study fills a research gap by investigating determinants of financial sector performance on sharia and conventional banks.